Influence of Timurid architecture on Safavid and Mughal mosques in India / Maryam Khazaee - Maryam, Khazaee (2015)
Before and after the advent of Islam, Persian architecture was heavily influential towards the structures of the Indian subcontinent. During the Mughal era (1526-1707AD), bilateral relations between Persia and India reached the highest level in all aspects of life. Even though the Mughal period was contemporaneous of the Safavid (1524-1736), many historical evidences hold that Mughal architecture was mostly influenced by the Timurid dynasty (1370-1526) more than Safavid architecture, with Timurid architecture serving as a prototype for both Safavid and Mughal styles. The main objective of this study is to investigate the influence of Timurid architectural elements (1370-1525) in Mughal mosques of India (1526- 1707AD). Mughal mosques were selected in this research due to the fact that despite the importance of mosques in the Islamic world. The main question is how Timurid architectural elements were transferred to and influenced Mughal buildings (1526-1707AD) in the Indian subcontinent. Hence, this research explored the Timurid architectural influence in Mughal mosques by examining the selected historical buildings using qualitative multiple case studies and by collecting multiple sources of data for each case study. The validation of research as a qualitative study involves triangulation, which means triangulating different sources and using it to build a coherent justification for the themes. Moreover, this research focused on the transfer of Timurid architectural elements that were innovated and inserted to the mosques of Persia by Persian master builders. These elements may be innovated in Timurid period or may have been developed and used from the pre-Timurid era. The five most important factors are ivan, domed chamber, double iv dome, squinch, and pointed arch. Each of these elements was closely examined during the course of the case study. By locating the historical evidences, the routs and channels of architectural influence could be defined and verified, and then the results of each case study analysed based on five architectural elements were compared in three phases to demonstrate the Timurid architectural influence in early and high Mughal periods separately. Finally, the evolution and alteration of Timurid influence during the Mughal period (early and high phases) were studied. The finding of the research highlighted that formal elements (both structural and ornamental), including pointed arch, squinch, and double domes could be used near the original faces with minimal changes in both early and high Mughal phases. While the domed chamber and ivan as functional elements were needed to match Mughal mosques due to the differences between Timurid and Mughal mosques in term of design and concept. Moreover, both functional elements in the early phase of the Mughal era have more levels of similarity with Timurid architecture compared to the high phase. Between the proportions of Ivans and domed chamber, the Ivans of Mughal mosque were more match to Timurid architecture .The vertical proportions of both functional elements in Mughal mosques were more match than the horizontal proportion to Timurid architecture.